Generations of freedom : gender, movement, and violence in Natchez, 1779-1865 - Ribianszky, Nik (Athens : University of Georgia Press, 2021)
"In Generations of Freedom: Gender, Movement, and Violence in Natchez, 1779-1865, Nik Ribianszky employs the lenses of gender and violence to examine family, community, and the tenacious struggles by which free Blacks claimed and maintained their freedom under shifting international governance, from Spanish colonial rule (1779-1795), through American acquisition (1795) and eventual statehood (established in 1817), and finally to slavery's legal demise in 1865"--
Movement and the Community of Free People of Color in Natchez -- Sexual Violence and Community Creation in Natchez -- Gendered Violence as a Mechanism of Control -- Challenges to One's Most Intimate Property : Themselves -- Threats to Property -- Networks of Friends and Family -- Movement across the Color Line : Racial Passing as Resistance.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 28, 2021).
eBooks on EBSCOhost
Keywords: Free African Americans -- Mississippi -- Natchez; African American women -- Violence against -- Mississippi -- Natchez; African American women -- Abuse of -- Mississippi -- Natchez; Noirs américains affranchis -- Mississippi -- Natchez; Noires américaines -- Violence envers -- Mississippi -- Natchez; African American women -- Violence against; Free African Americans; Mississippi -- Natchez; History